A177 BIRTH COHORT SCREENING FOR HEPATITIS C IN AN OUTPATIENT ENDOSCOPY UNIT: A PILOT STUDY. (1st March 2018) - Rai, M; Lowe, C; McKay, J; Joyce, L; Hookey, L; Flemming, J A
Abstract: Background: Chronic hepatitis C (HCV) is a curable asymptomatic infection that can progress to liver failure and hepatocellular carcinoma if left untreated. The Canadian Liver Foundation (CLF) recommends one-time HCV screening in all Canadians born from 1945–1975. A large proportion of outpatient endoscopic procedures are for colon cancer screening in this birth cohort providing an opportunity for HCV screening and linkage to HCV care. Aims: We aimed to assess the feasibility of developing a targeted birth-cohort HCV screening program in the outpatient endoscopy setting. Methods: This is a cross-sectional study of patients born from 1945–1975 presenting to the outpatient endoscopy unit at Hotel Dieu Hospital in Kingston, Ontario in September, 2016. Patients were scheduled for upper endoscopy, colonoscopy, and/or sigmoidoscopy. All patients were given written information on HCV and the CLF recommendation of birth-cohort screening. Patients were then asked to complete a short survey regarding previous HCV screening and acceptance of being screened during their endoscopy visit. Results: During a 30 day period, 95% (223/235) of eligible patients completed the survey. The cohort was 53% female with a median age of 59 years (IQR 52–66 years). 83% had either never been screened or were unaware of their HCV status. Overall, 87% of participants would be accepting of HCV screening during their endoscopy visit, 9% would not accept screening and 4% stated they were unsure. These results suggest that almost 2, 000 patients could be targeted for HCV screening in the endoscopy unit annually. Conclusions: Most patients born from 1945–1975 presenting for outpatient endoscopy have not been screened for HCV but are accepting of screening during their procedural visit. This identifies a target population for the development of an HCV screening program to increase HCV identification and facilitate linkage to HCV care. Funding Agencies: None